2022
DOI: 10.3390/foods11182817
|View full text |Cite
|
Sign up to set email alerts
|

Effects of High-Intensity Ultrasound Treatments on the Physicochemical and Structural Characteristics of Sodium Caseinate (SC) and the Stability of SC-Coated Oil-in-Water (O/W) Emulsions

Abstract: The effects of high-intensity ultrasound treatment (0, 3, 6, 9 min) on physicochemical and structural characteristics of SC and the storage, thermal and freeze–thaw stability of SC O/W emulsions were investigated. The results showed that ultrasound treatment reduced the particle size of SC, although there were no obvious changes in zeta potential, profiles and weights. Ultrasound treatment improved surface hydrophobicity and fluorescence intensity of SC and changed ultraviolet–visible (UV–Vis) spectroscopy but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 64 publications
(89 reference statements)
0
3
0
Order By: Relevance
“…The increased thermal stability of the ultrasonicated ZSP-stabilized emulsion is probably due to the decreased droplet size of the emulsion and the increased amount of proteins interfacially adsorbed, creating a more durable and thicker interfacial film, which aids in preserving the stability of the emulsion when subjected to heat treatment [37] . Similarly, the increased thermal stability was also observed in emulsions stabilized with ultrasonicated sodium caseinate [38] .…”
Section: Resultsmentioning
confidence: 61%
“…The increased thermal stability of the ultrasonicated ZSP-stabilized emulsion is probably due to the decreased droplet size of the emulsion and the increased amount of proteins interfacially adsorbed, creating a more durable and thicker interfacial film, which aids in preserving the stability of the emulsion when subjected to heat treatment [37] . Similarly, the increased thermal stability was also observed in emulsions stabilized with ultrasonicated sodium caseinate [38] .…”
Section: Resultsmentioning
confidence: 61%
“…Especially, since the fluorescence emission of Trp is very sensitive to the environment, it is always applied to verify modifications of protein tertiary structure [31] . Compared with the untreated MP sample, the structure of UMP after ultrasonic pretreatment was extended and more hydrophobic groups inside were exposed to the protein surface, and the fluorescence intensity showed and enhanced phenomenon [32] . As can be seen in Fig.…”
Section: Resultsmentioning
confidence: 94%
“…Regarding emulsion stability, EPI had significantly lower emulsion stability (69%) than the other samples, which might be due to its larger molecular size. The decrease in molecular size of ultrasound-treated or hydrolyzed samples resulted in increased emulsion stability [ 47 ]. O'Sullivan et al [ 27 ] also reported that large droplet sizes exhibited gravitational separation with a cream layer that was responsible for the instability of the emulsion.…”
Section: Resultsmentioning
confidence: 99%